Sedative load and anticholinergic burden among older adults in Slovenia over a decade: Potential for optimization of pharmacotherapy - Jazbar, Janja; Locatelli, Igor; Kos, Mitja (Acta Pharmaceutica, 2024)
This study investigates the 10-year trend in the sedative and anticholinergic burden among older adults in Slovenia, with the aim of identifying opportunities to optimize pharmacotherapy in this population. A retrospective drug utilization analysis was conducted based on a national anonymized database of dispensed prescriptions from 2009 to 2019. The study employed the sedative load model and the anticholinergic cognitive burden scale to assess the sedative and anti cholinergic burden, respectively. The findings indicate that in 2019, 45.6 % and 40.8 % of older adults (≥ 65 years) used sedative and anticholinergic medications, respectively. A high sedative load and a clinically significant anticholinergic burden were observed in a considerable proportion of older adults (13.2 % and 11.2 %, respectively, in 2019). The age-standardized prevalence of sedative load and anti-cholinergic burden significantly decreased over the 10-year study period by 5.6 % and 1.7 %, respectively (absolute difference), while the prevalence of clinically significant anticholinergic burden remained stable. Notably, the age groups 85–89 years and above 90 years had an increase in the proportion of individuals with a clinically significant anticholinergic burden over the years. These results emphasize the need for targeted interventions, particularly in the oldest age groups, to promote safe and effective medication use among older adults.